Antecedents of Performance of Employees of the Central Immigration Detention Center (Rudenim) Tanjungpinang City - Imran Ilyas; Anoesyirwan Moeins; Alex Zami (Pusat Riset dan Inovasi Nasional, 2023)
Purpose – This paper seeks to examine the effect of remuneration and work discipline on the performance of employees of the Central Immigration Detention Center (Rudenim) Tanjungpinang City. Methodology/approach – The type of research used in this study is quantitative descriptive. The sample in this study was all employees totaling 96 respondents. Data collection techniques carried out in the form of questionnaires, and literature studies. The analytical techniques used are validity tests, reliability tests, classical assumption tests, multiple linear regression tests and hypothesis tests with JASP. Findings – It was found that, remuneration affects employee performance and work discipline variables have a significant effect on employee performance. Overall, the variables of remuneration and work discipline affect employee performance. Novelty/value – As an employee, remuneration and work discipline are important factors in Tanjungpinang Rudenim in maintaining the performance of its employees.